Stakeholder Analysis on Planting and Utilization of Balsa in RPH Pandantoyo, BKPH Pare, KPH Kediri - Pratama, Moh Rizal; Purwawangsa, Handian (Journal of Tropical Silviculture, 2024)
Balsa planting in RPH Pandantoyo has benefits in economic, ecological, and social aspects. The objectives of this study were to identify stakeholders involved in balsa planting and utilisation activities, classify stakeholders based on their influence and importance on balsa planting and utilisation activities, and formulate a mechanism for relationships between stakeholders related to balsa planting and utilisation activities. Data collection was carried out using interviews and observations of stakeholders involved in the activities. The balsa planting programme involves Perhutani, LMDH Lancar Jaya, PT Bina Megah Indowood, and the village government. Based on the results of the assessment using the matrix of influence and importance, Perhutani, LMDH Lancar Jaya, PT Bina Megah Indowood are included in the key player category, and the village government is included in the crowd category. Keywords: Collaboration, planting and utizilation balsa, stakeholder